Mall Visit Behaviour of Older Generation -Y Consumers - Hemalatha, K G.; Ravickandran , K (Gyan Management Journal, 2009)
The retailing business in India has witnessed huge growth due to emergence of super markets. The Indian consumer is now being exposed to a variety of retail formats leading to change in consumer buying behavior. The objective of this research is lo investigate the relationship between hedonic motivations and demographic factors of oMer generation Y consumers. Primary data were collected using a structured - questionnaire and it was administered to 300 visitors of malls with the age group of 19 to 25 years.Principal Component analysis was applied for extracting factors along with orthogonal rotation with Varimax. It was found that six motivational factors drive the mall visit i.e. adventure shopping, social shopping, value shopping, role shopping, gratification shopping and idea shopping. The study is useful to the retailers to formulate suitable marketing strategies to attract the growing Indian generation Y consumer.